2017
DOI: 10.1007/s40266-017-0470-x
|View full text |Cite
|
Sign up to set email alerts
|

Falls-Related Drug Use and Risk of Falls Among Older Adults: A Study in a US Medicare Population

Abstract: BackgroundApproximately one-third of community-dwelling older adults fall each year, and approximately 10% have falls requiring medical services. Among other factors, research studies have linked certain medications with an increased risk of falls.ObjectiveThe aim of this study was to examine the risk of falls relative to use patterns among new and continuing falls-related drug (FRD) users.MethodsA 10% random sample, insured in AARP® Medicare Supplement and AARP Medicare Part D Rx plans, was utilized to define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
(76 reference statements)
0
27
1
2
Order By: Relevance
“…In this group there was not much difference between the number of comorbidities in the two groups and polypharmacy was also widely prevalent. A study by Musich et al, found that in new and continuing fall‐related drug (FRD) users the fall rates were 7% and 8%, respectively, which also provides a platform for the polygenetic etiology of falls. In a study by Early et al, it was noted that fall rates increased with >6 FRDs in the 65‐74 age group and >5 FRDs in the 75‐84 age group.…”
Section: Discussionmentioning
confidence: 99%
“…In this group there was not much difference between the number of comorbidities in the two groups and polypharmacy was also widely prevalent. A study by Musich et al, found that in new and continuing fall‐related drug (FRD) users the fall rates were 7% and 8%, respectively, which also provides a platform for the polygenetic etiology of falls. In a study by Early et al, it was noted that fall rates increased with >6 FRDs in the 65‐74 age group and >5 FRDs in the 75‐84 age group.…”
Section: Discussionmentioning
confidence: 99%
“…Sedation and postural hypotension by antidepressants and beta-blockers and the hypoglycemic effect of insulin also significantly contribute to the incidence of falls in the elderly. 5 , 18 , 37 , 38 In addition, the use of diuretics and laxatives cause the elderly to get up frequently and rush at a fast pace to use the toilet, usually without assistance thus increasing the risk of falls.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 14 , 15 , 16 Furthermore, cardiovascular drugs such as diuretics and beta-blockers may cause or worsen orthostatic hypotension and falls. 17 , 18 Antihistamines and anticholinergic drugs may affect the cognitive skills of elderly patients and cause blurred vision, thereby increasing the risk of falls. 19 It has also been stressed by the same authors that polypharmacy and the use of psychotropic drugs, especially when combined with cardiovascular medications increase the risk of falls in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, those in the older adult population are at risk of falls, and the use of drugs may increase the risk of falls. Most research regarding drug use and falls have focused on prescription drugs, not marijuana use ( Musich, Wang, Ruiz, Hawkins, & Wicker, 2017 ).…”
Section: Discussionmentioning
confidence: 99%